Factibilidad para la implementación de una planta procesadora de conserva de fríjol tierno (vigna sesquipedalis) - Centeno Sabando, Gabriela Nataly (2019)
The purpose of this study was to determine the feasibility of implementing a processing plant for tender bean (Vigna sesquipedalis). For this purpose, a non-experimental, descriptive and field type study was implemented, from which the factors that positively affect the location of the company to the georreferential location of the sector were identified. The plant will be located at the Ceibal site in Rocafuerte canton, at a distance of no more than five kilometers from the production sites and primary generation of raw material, which makes viable an adequate productive flow and timely delivery of orders. Of 175,946 kg / year that corresponds to the total demand, 10% (used capacity) will be used in the first year, and an apparent population of 23.5% was considered as potential consumption, which corresponds to the installed capacity of 354,405 kg approximately. The price study determined an appropriate range between $1.30 and $1.45. Additionally, the choice of the production capacity of the machinery was considered according to the installed capacity of equipment, raw materials and labor available to satisfy the demand. The present project estimated a Net Present Value (NPV) of $59,855.09 and an internal rate of return of 23% and an equilibrium point of $84,469.42. In this way, the economic and financial feasibility for the implementation of the bean processing plant in the Rocafuerte canton was determined.